2008
DOI: 10.1016/j.jpeds.2008.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Lactate to Creatinine Ratio and Neurodevelopmental Outcome in Term Infants with Hypoxic-Ischemic Encephalopathy

Abstract: Objective-To assess the association between urinary lactate to creatinine ratio (ULCR) and neurodevelopmental outcome in term infants with hypoxic ischemic encephalopathy and examine the effect of hypothermia on the change in ULCR.Study design-Spot urine samples were collected in 58 term infants (28 hypothermia, 30 control subjects) with hypoxic ischemic encephalopathy. Urinary lactate and creatinine were measured by using 1 H nuclear magnetic resonance spectroscopy and expressed as ULCR. Survivors were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Discussion S100B is predominantly expressed in the nervous system and has been well established as a biochemical marker for brain injuries [8][9][10] . The measurement of urinary S100B may provide an excellent sampling source for the biochemical markers in newborns with HIE [1,2] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion S100B is predominantly expressed in the nervous system and has been well established as a biochemical marker for brain injuries [8][9][10] . The measurement of urinary S100B may provide an excellent sampling source for the biochemical markers in newborns with HIE [1,2] .…”
Section: Resultsmentioning
confidence: 99%
“…The urinary lactate/ creatinine ratio may reflect the general metabolic conditions of the perinatal hypoxia and reperfusion damage. The use of the urinary lactate/creatinine ratio in predicting HIE has been established [1,10] . In the present study, the ratio was significantly increased in the newborns with different severity of HIE only on day 1 after birth, with higher ratios representing more severe cases.…”
Section: Resultsmentioning
confidence: 99%
“…A secondary analysis involving spot urine samples collected in 58 study participants revealed that a high urinary lactate=creatinine ratio was associated with death or disability (Oh et al, 2008). Lastly, detailed analysis of the randomized controlled trial data revealed safety of hypothermia during the intervention period and during follow-up to 18-22 months .…”
Section: Hyperthermia In Infants With Hypoxic-ischemic Encephalopathymentioning
confidence: 97%
“…19 Finally, a secondary analyses involving spot urine samples collected in 58 study participants, revealed that high urinary lactate to creatinine ratio was associated with death/disability. 20 There are important differences between the Cool Cap and the Whole Body Hypothermia Trial. The 2 trials use different entry criteria distinguished primarily by the use of the aEEG in the Cool Cap trail.…”
Section: Prevention Of Cp In Term and Near-term Infantsmentioning
confidence: 99%